The Reflection of Rural Society’s Life in the Novel Mantra Penjinak Ular by Kuntowijoyo A Study of Literature Sociology - Mardiani, Nani (Balai Bahasa Jawa Tengah, 2017)
This research aims in analyzing Mantra Pejinak Ular, a novel by Kuntowijoyo using sociology of literature approach. The Methods and technique applied in conducting this reseach are reading and understanding the novel completely, collecting and noting the data related to identify the cultural background of the novel Mantra Penjinak Ular by Kuntowijoyo. Furthermore, as sociological analysis of literature was done by investigating the social culture described in the novel Mantra Penjinak Ular. The result of this study is there are three social problems in this novel: cultural value, political value, and love value.?Keys Word: people, novel, Javanese culture, sociology of literature